Cellular and viral miRNA expression in polyomavirus BK infection. Issue 5 (29th August 2019) - Zeng, Gang; Wang, Zijie; Huang, Yuchen; Abedin, Zahidur; Liu, Yang; Randhawa, Parmjeet
Abstract: Polyomavirus BK (BKV) is an important pathogen in kidney transplant patients. Regulation of BKV encoded microRNAs (miRNAs) is not well understood. Therefore, tubular epithelial cells infected with BKV were examined for changes in small RNA expression. The observed changes were further evaluated by real‐time PCR and RNA‐seq analysis of renal allograft biopsies. BKV‐miR‐B1‐5p and BKV‐miR‐B1‐3p showed a 1000‐fold increase over 12 days but did not prevent cell lysis. Downregulation of host miR‐10b and miR‐30a could be confirmed on all three platforms evaluated. Whereas, the BKV genome expressed more 3p than 5p miRNA species, the reverse was true for the human genome. Decreased expression of TP53INP2, and increased expression of BCL2A1, IL‐6, IL8 and other proinflammatory cytokines were shown in biopsies with BKV nephropathy. No change in expression was seen in miR‐10a dependent expression of NKG2D ligands ULBP3, MICA, or MICB. In conclusion, BKV infection results in regulation of cellular genes regulated by and possibly amenable to therapies targeting miR‐10 and miR‐30.